Protocol to identify endogenous proximal proteins using biotinylation by antibody recognition - Camilla Rega; Mercedes Pardo; Lesley-Ann Martin; Jyoti Choudhary (STAR Protocols)
Summary: Biotinylation by antibody recognition (BAR) is an antibody-based approach for mapping proximal protein interactions in cells. Here, we present a protocol to biotinylate and identify proximal proteins using BAR. We describe steps for defining proximity labeling reaction conditions, assessing enrichment using western blot, and sample preparation for mass spectroscopy analysis. We then detail procedures for data analysis and identifying proximal proteins. This approach differs from standard proximity labeling techniques, which rely on genetically engineered enzymes fused to the target protein.For complete details on the use and execution of this protocol, please refer to Rega et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.